Inhibiting oxygen vacancies and twisting NbO6 octahedron in erbium modified KNN-based multifunctional ceramics - Lulu Gao; Zhiyong Liu; Pengrong Ren; Renhong Liang; Ting Li; Kun Guo; Bing Xie; Jinshan Lu; Pu Mao; Jun Tian; Longlong Shu (Journal of Materiomics, 2024)
It is a challenge to obtain highly tunable multifunctional performances in one ferroelectric system by a simple approach to meet the miniaturization, integration, and functionalization requirements of advanced electronic components. Herein, rare earth erbium (Er) modulated 0.9K0.5Na0.5NbO3-0.1Sr(1-x)ErxTi(1-x/4)O3, (0.9KNN-0.1ST: xEr) transparent-photoluminescent-ferroelectric energy storage multifunctional ceramics are prepared to solve this problem. The effect of lattice distortion and oxygen vacancies by Er doping on the optical and electrical properties is systematically investigated. The Er3+ ions can introduce a large distortion of the NbO6 octahedron by replacing the A-site in KNN-based ceramics. Thanks to the higher c/a ratio and lower oxygen vacancy content are simultaneously obtained in 0.9KNN-0.1ST: 0.1Er ceramics. The effective energy storage density (Wrec) of 0.86 J/cm3, excellent near-infrared transmittance of 51.7% (1 100 nm) and strong green upconversion photoluminescence are achieved in this multifunctional ceramic. This study provides a solid basis for rare earth ions doped ferroelectric ceramics with tunable multifunctional properties and has significant potential for applications in optoelectronic devices.